Fraud Hexagon Theory dalam Mendeteksi Kecurangan Laporan Keuangan pada Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Ima Mukaromah; Gideon Setyo Budiwitjaksono (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
This study aims to examine and analyze the effect of hexagon fraud which is proxied by financial stability, financial targets, external pressure, cooperation with government projects, change of directors, ineffective monitoring, turnover of auditors, the ratio of total accruals to total assets, external auditors quality, and the company's existence towards fraudulent financial statements in banks listed on the BEI 2015-2019. The sampling method used was purposive sampling technique and obtained a sample of 29 companies with 145 data. The type of data used is secondary data from annual banking reports. Data were analyzed using SEM PLS with WarpPLS 7.0 software. The research results prove that financial stability, financial targets, and ineffectiveness of monitoring have an effect on fraudulent financial statements. Meanwhile, external pressure, cooperation with government projects, change of directors, change of auditors, ratio of total accruals to total assets, external auditors quality, and the existence of companies have no effect on fraudulent financial statements.